Using chemometrics and near-infrared reflectance spectroscopy for discrimination of poultry meat and prediction of cholesterol content - Gąsior, Robert; Wróblewski, Wojciech; Połtowicz, Katarzyna (2018)
Four calibrations were made for cholesterol content in poultry meat (breasts and legs from chickens, cockerels, capons, and breasts and legs from geese). Standard uncertainties expressed as SECV (%, relative) for chickens, cockerels and capons were 9.2 for breasts and 7.8 for legs. These values for geese were 8.4 and 9.0, respectively. The discriminant method with the highest predictive ability, based on residuals RMSX Residents, was used to classify the samples. Classification accuracy values were good and ranged, on average, from 96.8% to 98%. The NIRS calibrations on cholesterol content in the breast and leg meat of chickens, capons, cockerels, as well as in the breast and leg meat of geese, are suitable for rapid routine analyses to use in practice.
Provedene su četiri kalibracije za sadržaj kolesterola u mesu peradi (prsa i bataci pilića, pijetlića, kopuna i gusaka). Standardne kolebljivosti izražene kao SECV (Standardna pogreška rotirajuće procjene) (%, relativno) za piliće, pijetliće i kopune bile su 9,2 za prsa i 7,8 za batake. Te su vrijednosti za guske iznosile 8,4 odnosno 9,0. Metoda diskriminacije s najvećom mogućnošću predviđanja na temelju RMSX Residents korištena je za klasificiranje uzoraka. Vrijednosti točnosti klasifikacije bile su dobre i kretale su se, uglavnom, od 96,8% do 98%. Kalibracije NIRS za sadržaj kolesterola u mesu prsa i bataka pilića, kopuna, pijetlića kao i mesu prsa i bataka gusaka dobre su za brzu rutinsku analizu u praksi.
Bibliografija: 22 jed.
Summary ; Sažetak.
Keywords: Kolesterol -- Meso peradi -- Rotirajuća procjena